At Which Level Does Unemployment Affect Political Trust? A Multilevel Analysis Across Europe - Leo Azzollini; Ebru Sanlitürk; Vytenis Deimantas; Selin Köksal (Social Indicators Research, 2025)
How does unemployment at the national, regional, and individual levels affect political trust in Europe? Previous research has assessed the negative impact of unemployment at the national and individual levels on political trust. However, the literature has not yet addressed the interactions between unemployment dynamics across levels, which are increasingly relevant in socio-political research. In this article, we posit that national, regional, and individual unemployment depress political trust and formulate hypotheses on their interactions, integrating perspectives from sociology, social psychology, and political science. We test these hypotheses relying on Rounds 4–9 (2008–2018) of the European Social Survey, for 28 countries, 218 regions, and 877 region-years. Results from three-level multilevel models with cross-level interactions indicate that individual and national unemployment are associated with lower political trust, although their interaction is unclear. In contrast, there are significant interactions between regional and individual unemployment levels. A Fairbrother decomposition further clarifies this pattern: lower average regional unemployment rates powerfully exacerbate the individual relationship, while the latter is mitigated at higher average unemployment rates. Robustness checks with linear regressions and country-year fixed effects reinforce the main results. Theoretically, these empirical patterns support the habituation mechanism emerging from related research on socio-political behaviour, and they thus illuminate the joint centrality of contextual and individual socio-economic hardships to understand political trust, which is crucial for the health of democracies.
Keywords: 300; Political trust; Unemployment; Habituation; Multilevel; Europe; European social survey